Epidemiology of Taenia saginata taeniosis/cysticercosis: A systematic review of the distribution in southern and eastern Africa - Dermauw, Veronique; Dorny, P.; Braae, U.C.; Devleesschauwer, Brecht; Robertson, L.J.; Saratsis, A.; Thomas, Lian F. (Springer, 2018)
The beef tapeworm, Taenia saginata, causing cysticercosis in bovines and taeniosis in humans, is thought to have a global distribution. In eastern and southern Africa, cattle production plays a crucial role in the economy, but a clear overview of the prevalence of T. saginata in the region is still lacking. This review aims to summarize existing knowledge on T. saginata taeniosis and bovine cysticercosis distribution in eastern and southern Africa. A systematic review was conducted, that gathered published and grey literature, including OIE reports, concerning T. saginata taeniosis and bovine cysticercosis in eastern and southern Africa published between January 1st, 1990 and December 31st, 2017. A total of 1232 records were initially retrieved, with 78 full text articles retained for inclusion in the database. Unspecified taeniosis cases were reported for Angola, Ethiopia, Kenya, Madagascar, Malawi, South Africa, Tanzania, Uganda and Zambia, whereas T. saginata taeniosis cases were found for Ethiopia, Kenya, South Africa, Tanzania, Zambia and Zimbabwe. The prevalence of taeniosis ranged between 0.2–8.1% based on microscopy, and between 0.12–19.7% based on coproAg-ELISA. In Ethiopia, the percentage of tapeworm self-reporting was high (45.0–64.2%), and a substantial number of anthelmintic treatments were reported to be sold in towns. The presence of bovine cysticercosis was reported in all 27 countries/territories included in the study, except for Rwanda and Somalia, Comoros, Madagascar, Mauritius, Mayotte, Seychelles and Socotra. The prevalence of cysticercosis ranged between 0.02–26.3% based on meat inspection, and between 6.1–34.9% based on Ag-ELISA. Although T. saginata has been reported in the majority of countries/territories of the study area, T. saginata taeniosis/cysticercosis remains a largely ignored condition, probably due to the absence of symptoms in cattle, the lack of data on its economic impact, and the fact that human taeniosis is considered a minor health problem. However, the occurrence of bovine cysticercosis is a clear sign of inadequate sanitation, insufficient meat inspection, and culinary habits that may favour transmission. Measures to reduce transmission of T. saginata are therefore warranted and the infection should be properly monitored.